BOARDGAME ULAR TANGGA BERBASIS AUGMENTED REALITY DENGAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MATERI KERAGAMAN BUDAYA - Dwi Lestariningsih; Sutrisna Wibawa; Heri Maria Zulfiati (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
The 21st century is the era of industrial revolution 4.0 where technology integration is very necessary in learning. One technology that can be applied in learning is Augmented Reality (AR). This research is development research (Research and Development) with the aim of producing a product in the form of an Augmented Reality Based Snakes and Ladders Board Game with a Problem Based Learning Model to Improve Critical Thinking Skills on Cultural Diversity Material. The development procedure uses the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. Data collection techniques in the preliminary study were in the form of interviews and documentation, while in implementation it was in the form of interviews, observation and documentation. The instruments in this research are interview instruments for needs analysis, media expert and material expert validation sheets, student and teacher interview instruments, and test questions. The test results show a Sig value. (2-tailed) or Two-Sided < 0.01 with a standard deviation of 4,582. This value shows that the significance level is less than 0.05, so it can be concluded that there is a significant difference between the results obtained before and after using the augmented reality-based snakes and ladders board game media. Based on this, it can be concluded that the use of the Augmented Reality-based snakes and ladders board game media is effective in increasing the achievement of learning objectives regarding cultural diversity material.